Expression profile of plasma microRNAs and target genes in patients with complicated pregnancy - M. D. Umerova; S. S. Alyadinova; M. J. Khonjonova; R. A. Balakadasheva; E. E. Menadzhiev; D. I. Kharchuk; D. O. Leus; G. I. Islyamova; M. I. Islyamova; S. L. Abkarimova; D. S. Kasabyan; L. E. Sorokina (Акушерство, гинекология и репродукция, 2023)
Aim: to assess features of placental transcriptome in patients with complicated pregnancy course and outcome.Materials and Methods. A prospective observational comparative study in parallel groups was carried out by examining 44 patients divided into three groups: group 1 included 13 pregnant women with moderate and severe preeclampsia (PE), group 2 consisted of 12 patients with fetal growth retardation (FGR), control group included 19 clinically healthy women with uncomplicated pregnancy and delivery. All women enrolled to the study underwent a comprehensive examination, including history collection, general and obstetric-gynecological examination, laboratory and instrumental studies. Special research methods were used during the study, which included placental tissue sampling followed by analyzed expression profile of 12 microRNAs using real-time polymerase chain reaction (PCR).Results. The PCR data indicated about lack of expression for analyzed miR-210-3p, miR-320-3p, miR-1304-5p and miR-375-5p in placental tissue samples in FGR patients. No significant differences in placental miRNA levels were observed in FGR vs. PE and control group. Analysis of placenta-specific microRNAs in women with PE vs. control group showed a significantly down modulated expression level for miR-517a-3p (p = 0.025), miR-517c-3p (p = 0.036), miR-574-5p (p = 0.015) along with upregulated expression of miR-20a-5p (p = 0.046).Conclusion. The data obtained evidence that pregnancy-related complications are characterized by specific molecular changes at placental transcriptome level.